PENGARUH KEGIATAN MENGGAMBAR DENGAN MEDIA ADONAN TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DI TK LABOR FKIP UR KECAMATAN TAMPAN KOTA PEKANBARU - Zarifah Oktavia; Zulkifli N Zulkifli N; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to investigate the influence of drawing activity by dough media toward child’s fine motor skills 4 to 5 years old. This research was done at TK Labor FKIP UR Tampan Sub - District Pekanbaru City for November 2017. This research was experiment one group pre-test post-test design by total sample 19 children consist of 10 male and 9 female. The instrument was observation sheet to note the activities for treatment. Based on the hypothesis test was gotten the influence of of drawing activity by dough media toward child’s fine motor skills 4 to 5 years old. This research was done at TK Labor FKIP UR Tampan Sub - District Pekanbaru City. The score of tcount is 29,502 by sig 0,020, because sig < 0.05 it can be concluded that there is the influence of drawing activity by dough media toward child’s fine motor skills. On the hypothesis test can be seen tcount 29,502 >t table = 1,734. It means that there is a significant influence drawing activity by dough media toward child’s fine motor skills 4 to 5 years old. This research was done at TK Labor FKIP UR Tampan Sub - District Pekanbaru City is 60,19%.Keywords: Fine Motor Skills, Influence Drawing Activity, Dough Media